The dark matter puzzle in a class of models with gauge symmetry SU(3)C ⊗ SU(3)L ⊗ U(1)N. Issue 1 (28th March 2019) - Alvarez‐Salazar, C. E.; Peres, O. L. G.; Sánchez‐Vega, B. L.
Abstract : We analyze the dark matter (DM) puzzle in a class of models with gauge symmetry SU(3) C ⊗ SU(3) L ⊗ U(1) N, taking into account the constraints coming from Planck observations of the DM relic density, direct detection searches with Xenon1T, and indirect detection using Fermi‐LAT data. The model has two possible candidates, a fermion and a scalar, which require, to evade the constraints set by Xenon1T and Fermi‐LAT, and have relic densities in the range measured by the Planck collaboration, a minimum vacuum expectation value to break the SU(3) L symmetry of 10 and 15 TeV, respectively. In this case, these particles have masses of order 1 TeV, for the fermion, and between 500 and 600 GeV, for the scalar.